Biofertilizer composition - Othman, Radziah; Naher, Umme Aminun; Panhwar, Qurban Ali (2012)
The present invention relates to a biofertilizer that is used to enhance plant growth. The biofertilizer composition comprises of a fungi and a consortium of bacterial strains. The consortium of bacterial strains comprising of at least a Bacillus spp. strain and at least a Stenotrophomonas sp. strain isolated from rice rhizosphere. Upon utilization, uptake of nitrogen and phosphate by the plant is enhanced due to presence of nitrogen fixing bacteria and phosphate solubilizing bacteria.